Diagnostic accuracy of high-resolution peripheral quantitative computed tomography and X-ray for classifying erosive rheumatoid arthritis - Klose-Jensen, Rasmus; Therkildsen, Josephine; Blavnsfeldt, Anne-Birgitte Garm; Langdahl, Bente L; Zejden, Anna; Thygesen, Jesper; Keller, Kresten Krarup; Hauge, Ellen-Margrethe (Rheumatology (Oxford, England), 2022)
Abstract Objective To investigate whether high-resolution peripheral quantitative CT (HR-pQCT) of two metacarpophalangeal (MCP) joints can more accurately classify patients as having erosive RA compared with conventional radiography (CR) of 44 joints in the hands, wrists and feet. Methods In this single-centre cross-sectional study, patients with established RA (disease duration ≥5 years) were investigated by HR-pQCT and CR. The second and third MCP joints of the dominant hand were assessed for erosions by HR-pQCT. CR of the hands, wrists and feet were scored according to the Sharp–van der Heijde (SHS) method. Results In total, 353 patients were included; 66 (18.7%) patients were classified as having non-erosive RA, and 287 (81.3%) had erosive RA by CR. The sensitivity and specificity (95% CI) of HR-pQCT for classifying patients as having erosive RA when standard CR of hands, wrists and feet was used as the reference was 89% (84, 92%) and 30% (20, 43%), respectively. Using HR-pQCT as the reference, the sensitivity and specificity of CR for classifying patients having erosive RA were 85% (80, 89%) and 38% (25, 52%), respectively. McNemar’s χ2 test showed no significant difference between the sensitivities of patients classified as having erosive RA by HR-pQCT or by CR (2.14, P = 0.177). Conclusion The diagnostic accuracy of HR-pQCT scanning of only two MCP joints and CR of 44 joints suggests the two modalities were comparable for classifying patients with established RA as having erosive disease. Clinical trial registration ClinicalTrials.gov (NCT03429426).